COOPERATION IN WORK-ORIENTED LEARNING IN HIGHER EDUCATION - Houston, Muir; Krüger, Karsten; Molas, Alba; Osborne, Mike; Jiménez, Laureano (PEOPLE: International Journal of Social Sciences, 2016)
The paper reports on preliminary findings from an EU funded project on collaboration and partnership between external stakeholders and universities to deliver work-related learning to adults with existing labour market experience in order to increase skills and competences for the knowledge economy as envisaged in Agenda 2020. The paper engages with debates on the professionalization of vocational education and consequently the vocationalisation of university education. It reports relevant data for the six partner countries of the LETAE project and EU averages to provide some context to debates about relative levels of attainment and labour market position. It briefly introduces some data drawn from cases studies of work-related learning in higher education delivered in partnership or collaboration with external stakeholders including local authorities, trade unions, and individual enterprises. Finally, it compares in detail the cases from the UK and Spain as illustrative of specific national responses to work-related learning initiatives.